Development of Rapid Response Capabilities in a Large COVID-19 Alternate Care Site Using Failure Modes and Effect Analysis with In Situ Simulation. (November 2020) - Levy, Nadav; Zucco, Liana; Ehrlichman, Richard J.; Hirschberg, Ronald E.; Hutton Johnson, Stacy; Yaffe, Michael B.; Ramachandran, Satya Krishna; Bose, Somnath; Leibowitz, Akiva
Abstract : Preparedness measures for the anticipated surge of coronavirus disease 2019 (COVID-19) cases within eastern Massachusetts included the establishment of alternate care sites (field hospitals). Boston Hope hospital was set up within the Boston Convention and Exhibition Center to provide low-acuity care for COVID-19 patients and to support local healthcare systems. However, early recognition of the need to provide higher levels of care, or critical care for the potential deterioration of patients recovering from COVID-19, prompted the development of a hybrid acute care–intensive care unit. We describe our experience of implementing rapid response capabilities of this innovative ad hoc unit. Combining quality improvement tools for hazards detection and testing through in situ simulation successfully identified several operational hurdles. Through rapid continuous analysis and iterative change, we implemented appropriate mitigation strategies and established rapid response and rescue capabilities. This study provides a framework for future planning of high-acuity services within a unique field hospital setting. Abstract : Rapid response and critical care capabilities were established within a COVID-19 field hospital serving Eastern Massachusetts. Successful implementation of this service through continuous analysis, iterative change, and in situ simulation provides a framework for future planning.